KONSEPSI APLIKASI DATABASE PERSONEL DALAM PENERBITAN SURAT PERINTAH DI AAL GUNA MENGHINDARI DUPLIKASI PENUNJUKAN PERSONEL - Salma Amalia Zakaria; A.H. Fadli; Satrio Teguh Amandiri (Saintek: Jurnal Sains Teknologi dan Profesi Akademi Angkatan Laut, 2021)
The Naval Academy is a municipality that oversees 18 work units. Each Satkerhas its own function. One of its functions is to issue warrants. At the Naval Academy,there are 2 work units that have the right to issue personnel warrants, namely Ditpers(Sub-Directorate of Minpers and Sub-Directorate of Watpers) and Denma. In practice,the manufacture of warrants still encounters problems, in the form of duplication ofpersonnel warrants because the data held by each work units issuing warrants hasnot been synchronized. This results in data updates in one Satker not being known byother work units unless the Satker staff provide information to other work units. Lackof coordination can lead to duplication of personnel warrants at the same time withdifferent activities. In the end, the orders given by superiors could not be carried outproperly or problems occurred in their implementation. The result of writing this thesis isa conception of a personnel database application that can be accessed simultaneouslyby each working unit that functions in the issuance of personnel personnel warrantat AAL. With this application, it is hoped that it will simplify the process of managingpersonnel data and publishing personnel personnel warrant at AAL.